The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/0890207021996970
|View full text |Cite
|
Sign up to set email alerts
|

Does personality predict responses to the COVID-19 crisis? Evidence from a prospective large-scale study

Abstract: The COVID-19 pandemic has significantly disrupted people’s daily routines and infused their lives with considerable insecurity and uncertainty. However, individuals’ responses to the pandemic vary widely. The present study investigates the role of personality traits for key aspects of people’s responses to the COVID-19 crisis. In a prospective design using a large-scale panel study ( N = 2217) that represents the heterogeneity of the adult population in Germany, we examined whether Big Five domains and facets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 38 publications
0
51
0
1
Order By: Relevance
“… 11 , 18 A few recent cross‐sectional studies support the hypothesis that specific personality traits are associated with specific psychosocial responses to COVID‐19 in the general population. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“… 11 , 18 A few recent cross‐sectional studies support the hypothesis that specific personality traits are associated with specific psychosocial responses to COVID‐19 in the general population. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneity in the assesment measures and the theoretical frameworks adopted in previous studies might explain incongruent findings. For instance, Rammstedt et al (2021) found that risk perception was not uniformly related to all the facets of agreeableness since it was correlated mainly with the trust facet. However, the questionnaire we used did not allow such refined profiling of personality facets.…”
Section: Discussionmentioning
confidence: 99%
“…However, the questionnaire we used did not allow such refined profiling of personality facets. Yet, research on the role of personality traits in perceiving the risk for COVID-like diseases is limited (Commodari, 2017;Commodari et al, 2020;Oljača et al, 2020;Rammstedt et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, combined with the finding that clustering appears to be more viable than demographics as a determinant of adversity responses, suggests that nuances in personality and environmental factors should be considered for identifying predictors of coping and adherence in future research. For example, individuals with high scores on the "Big Five" personality domain "Agreeableness" may be more inclined to comply with policy measures against COVID-19, while individuals with lower emotional stability tend to hoard supplies and fear financial [45,46].…”
Section: Discussionmentioning
confidence: 99%